Stormy times. Civic engagement in wind power development: Between support and rejection - Albert Roßmeier; Florian Weber ("All change please!": Challenges and opportunities of the energy transition, 2022)
Power generation in Germany is increasingly moving from the use of fossil fuels and nuclear power towards renewable energy. A significant 'pillar' of this transition is the use of wind power. However, despite high levels of general support for the energy transition, there is an increasing amount of civic protest against the construction of wind turbines. This article aims to explore the range of the key patterns of argumentation used by citizens' initiatives, some of which support and some of which oppose the further development of wind power. Discourse analysis is used to identify centrally anchored patterns within the structures of the arguments used by the protest movements in order to shed light on the discursive field of the energy transition. The key areas of conflict in the negotiation processes are multifaceted, spanning from economic or health-related aspects to issues related in particular to the topic of landscape and the legal frameworks of nature conservation. Both supporters and opponents refer to these issues - although using significantly differing arguments.
urn:nbn:de:0156-41340680; hdl:10419/250056; https://econpapers.repec.org/RePEc:zbw:arlabe:32
Keywords: 710; energy transition; wind power development; discourse analysis; power of social resistance; citizens' initiatives and protest